REKONSTRUKSI TARI BEDHAYA DIRADA META DI MANGKUNEGARAN - Nur Rokhim (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2012)
This article is the result of a study into the reconstruction of the BedhayaDiradaMeta dance in theMangkunegaran.This dance is interesting in that it uses the name Bedhaya and is performed by seven male dancers. The battle whichMangkunegara I experienced in the forest of Sitakepyak on the day of Monday Pahing 17 Sura in the year Wawu1681J/1756 AD was the event which inspired the creation of Bedhaya Dirada Meta. The meaning of the BedhayaDiradaMeta dance is closely related to the philosophy ofMangkunegara I’s struggle, promoting the concept of Islamicteachings (Sufism). In addition to this concept, the use of seven dancers is related to the events experienced byMangkunegaraI when he was fighting against theDutch. A socio-cultural approach was used, taken fromthe field of social and politicalsciences. In order to discover the history ofMangkunegara I’s struggle, in relation to existing texts ormanuscripts, a literary(hermeneutic) framework was used, with a historical method, in order to obtain reliable data. The reconstruction of theBedhayaDiradaMeta dance by Daryono, Hartanto, andWahyu Santoso Prabawa, was founded on the problem ofcreativity in the field of dance.Keywords: Reconstruction, BedhayaDiradaMeta dance.